Hubungan Motivasi Orang Tua dengan Hasil Belajar Siswa pada Mata Pelajaran Geografi - Handelia Mawi; Kalvin Salindeho Andaria; Hilda Vemy Oroh (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
The purpose of this study is to ascertain the connection between parental motivation and academic accomplishment. The research technique employed is a quantitative correlation method. strategies for gathering data include observation, interviews, questionnaires, and documentation. The t test and product moment correlation test are both used in the analysis technique. The results demonstrated that parental motivation had an impact on students' learning outcomes at SMA Negeri 3 Tana Toraja in geography as indicated by tcount = 31,854 > ttable 2,015, and the determinant coefficient was 85%, meaning that parental motivational variables accounted for 85% of the variance in students' learning outcomes and that the remaining 15% was influenced by other factors. Parental motivation is a strong predictor of student learning results. Parents' behavior is adequate to inspire youngsters to engage in learning activities